Primary oxide (Pt-oH) latent storage induced spillover and reversible electrocatalysts for oxygen electrode reactions - Jelena M. Jakšić (Zaštita Materijala)
Primary oxide (Pt-OH) latent storage and electrocatalytic spillover properties for the reversible oxygen electrode (ROE) behavior have been identified and substantiated, back and forth, all along the potential axis between hydrogen and oxygen evolving limits. Such advanced electrocatalytic properties imply interactive (SMSI - Strong Metal-Support Interaction) nanostructured Pt (Au, RuPt) clusters grafting upon composite mixed valence hypo-d-(f)-oxide supports, the latter featuring extra high stability and pronounced electronic conductivity, along with spontaneous dissociative water molecules adsorption, and resulting renewable primary oxide latent storage by continuous vapor supply and membrane type hydroxide ions surface migration. The latter as individual species, under imposed polarization transfer their prevailing part of electrons to the metallic electrocatalyst, thence resulting as Pt-OH (Au-OH) dipoles, and by their surface repulsion obey reversible spillover distribution and impose the electrocatalytic ROE properties all over the catalyst surface and DL pseudo-capacitance charging and discharging.